Pengaruh Kebijakan Dividen Dan Nilai Tukar Terhadap Harga Saham Dengan Profitabilitas Sebagai Variabel Intervening Pada Perusahaan Manufaktur Yang Terdaftar Di BEI - Clara Nodia Lase (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to analyze the effect of dividend policy and exchange rates on stock prices with profitability as an intervening variable in manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange for the period 2020–2024. The research population includes 94 manufacturing companies in the food and beverage sub-sector, with a sample of 24 companies selected using the purposive sampling method, resulting in 120 observations over five years. The research design employs a quantitative approach with secondary data analyzed using multiple linear regression and path analysis through SPSS version 26. The results indicate that dividend policy has no significant effect on profitability (t = -1.161; p = 0.248 > 0.05) or on stock prices (t = -1.501; p = 0.136 > 0.05). Exchange rates also have no significant effect on profitability (t = 0.455; p = 0.65 > 0.05) or stock prices (t = -0.968; p = 0.335 > 0.05). Meanwhile, profitability has a significant positive effect on stock prices (t = 6.532; p = 0.000 < 0.05). Simultaneously, dividend policy, exchange rates, and profitability significantly affect stock prices with an F value of 16.000 (p < 0.001) and a coefficient of determination (Adjusted R²) of 0.274 or 27.4%. Path analysis results show that profitability cannot mediate the effect of dividend policy on stock prices (indirect effect = -0.054 < direct effect = -0.118), but profitability can mediate the effect of exchange rates on stock prices (indirect effect = 0.021 > direct effect = -0.076). These findings confirm that profitability is a key factor influencing stock prices of manufacturing companies in the food and beverage sub-sector in Indonesia.